Analysis of hotels with cinema - Pisarieva, Olena; Holikova, Tatiana (My University, 2015)
The film industry in Ukraine and all over the world develops more and more, so amount of movie theaters increase. Hospitality industry also does not stand still. The hotels start to open cinemas where visitors can not only watch the movie, but if necessary to hold a conference or any other event. Paper presents some hotels with cinemas.
Keywords: movie theaters; movie; film industry; кінотеатри; кіноіндустрія; фільм; кафедра готельно-ресторанної справи